2010
DOI: 10.1016/j.ijrobp.2009.03.078
|View full text |Cite|
|
Sign up to set email alerts
|

Radiation Dose–Volume Effects in Radiation-Induced Rectal Injury

Abstract: The available dose/volume/outcome data for rectal injury were reviewed. The volume of rectum receiving ≥60Gy is consistently associated with the risk of Grade ≥2 rectal toxicity or rectal bleeding. Parameters for the Lyman-Kutcher-Burman normal tissue complication probability model from four clinical series are remarkably consistent, suggesting that high doses are predominant in determining the risk of toxicity. The best overall estimates (95% confidence interval) of the Lyman-Kutcher-Burman model parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
350
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(377 citation statements)
references
References 36 publications
(47 reference statements)
21
350
1
5
Order By: Relevance
“…This was demonstrated dosimetrically herein as the number of daily sessions receiving high rectum or bladder dose was reduced with decrease in margin. Based on previous reports, 1 , 2 , 35 rectum sparing is likely to translate into a decreased rate and level of late GI toxicity. The decrease of dose to the bladder may alleviate GU complications in the setting of standard fractionation and with prostate SBRT, which has shown higher (15.6%) late GU toxicity rate than that (12.6%) of the standard‐fractionated IMRT (36) …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This was demonstrated dosimetrically herein as the number of daily sessions receiving high rectum or bladder dose was reduced with decrease in margin. Based on previous reports, 1 , 2 , 35 rectum sparing is likely to translate into a decreased rate and level of late GI toxicity. The decrease of dose to the bladder may alleviate GU complications in the setting of standard fractionation and with prostate SBRT, which has shown higher (15.6%) late GU toxicity rate than that (12.6%) of the standard‐fractionated IMRT (36) …”
Section: Discussionmentioning
confidence: 95%
“…Daily rectal dose with an equivalent of normalV70Gy>30%,>25%,>20%, and>10% was analyzed. normalV70Gy>20% has been consistently associated with rectal bleeding or Grade ≥ 2 late rectal toxicity (1) . The endpoint of bladder was chosen as normalV65Gy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of intermediate‐ and low‐dose spillage caused by MLC rotation, intermediate‐ and low‐dose areas were predominant in the rectum. According to parameters of the Lyman–Kutcher–Burman normal tissue complication probability model from four clinical series, Michaslski suggested that high doses are crucial for determining the risk of rectal toxicity 24. Thus, we can infer that MLC rotation does not increase the risk of late rectal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The term gEUD is the generalized equivalent uniform dose which accounts for the fact that the rectum does not receive a uniform dose during treatment and is calculated according to the Kutcher–Burman histogram dose reduction method,32 gEUD=][1Nvoxelsfalse∑i=1NvoxelsDi1/nn,where N voxels is the number of voxels, D i is the dose to the i th voxel, and n is the volume effect factor, which models how the tolerance dose changes as the fractional volume of the rectum irradiated changes. To evaluate a minimum of grade 2 rectal toxicity, QUANTEC‐recommended parameters were used 33. They are as follows: n  = 0.09 (0.04 – 0.14), m  = 0.13 (0.1 – 0.17), and TD 50  = 76.9 Gy (73.7 – 80.1).…”
Section: Methodsmentioning
confidence: 99%